Natural Resource Management for tackling dual problems of water logging and irrigation water scarcity - Ranade, Deepak Hari; Mujalde, Santosh; Swarup, Indu (Indian Farming, 2018)
Studies show that assessing the site specific problem and then providing its solution scientifically can enhance the crop productivity in the fields otherwise lying unused or underused due to various reasons related to natural resource management aspects. In the present case too, a dual problem of waterlogging and water scarcity was tackled successfully by following principles of soil and water management by providing suitable drainage system and by constructing water storage structure in participatory mode by dovetailing and convergence process. Many site specific problems related to natural resource management still exist in the region and can be tackled scientifically.